Bean, Adzuki—Phaseolus angularis (Willd.) W.F. Wight - James M. Stephens (EDIS)
This document provides an overview of adzuki beans (Phaseolus angularis), highlighting their origin, cultivation, and uses. Adzuki beans, primarily grown in Japan and China, are valued for their sweet taste and versatility in culinary applications. The plant is described as erect, with yellow flowers and small cylindrical pods. Adzuki beans require about 120 days to mature and are best planted in frost-free periods. They are drought-resistant and highly nutritious, containing 25% protein. The beans can be used as dry beans, sprouts, or in desserts, and should be stored in a sealed jar in the refrigerator. Original publication date April 1994.